The use of space images for the assessment of the value of forest industry enterprises (Путеводитель предпринимателя)
The article discusses the possibilities and peculiarities of determination of economic efficiency of using space information in studies of forests and the use of new techniques and technologies for the decision of a number of tasks and problems of the organization of regular space shooting in the interests of the Russian forestry.